Rate and Predictors of Neonatal Jaundice in Northwest Ethiopia: Prospective Cohort Study - Birhanu, Molla Yigzaw (J Multidiscip Healthc, 2021)
BACKGROUND: Neonatal jaundice is one of the most common clinical disorders occurred worldwide. About 1.1 million neonates develop jaundice per year globally and the vast majority of them found in sub-Saharan Africa and South Asia. There is a paucity of evidence on the incidence rate and predictors of neonatal jaundice in Ethiopia. Therefore, this study was aimed at determining the rate and predictors of neonatal jaundice in the northwest, Ethiopia. METHODS: A prospective cohort study design was conducted at Debre Markos comprehensive, specialized Hospitals using 334 neonates from October 1, 2019, to June 30, 2020. Using a systematic random sampling technique, the study subjects were drawn. Data were entered into the Epi-Data(TM) Version 4.2 and analyzed using STATA(TM) Version 14.0. The Kaplan-Meier survival curve was used to estimate the survival time. A generalized Log rank test was used to compare the survival curves of different categorical variables. Finally, both bi-variable and multivariable Cox-proportional hazards regression models were used to identify the predictors of neonatal jaundice. THE RESULTS: The overall incidence rate of jaundice among neonates was 4.5 per 100 person-hours. Long duration of labor [ARR = 3.5; 95% confidence interval (CI), (2.8–8.7)], being male neonates [ARR= 5.2; 95% CI (3.5–7.3)], “O” blood group mothers [ARR = 4.5; 95% CI (3.4–10.3)], and having neonatal sepsis 3.4 [ARR=3.4; 95% CI: (2.5–6.1)] were predictors. CONCLUSION: The incidence rate of jaundice was higher in this study than the finding of the previous one. Being male, prolonged duration of labor, “O” blood group mothers and sepsis were the significant predictors. Hence, an effort has to be made to decrease the incidence rate of neonatal jaundice through improving newborn care and timely intervention for neonates with sepsis and delivered at a long duration of time as well as the neonates born from “o” blood type mothers are our recommendation.